ANALISIS KOORDINASI PESAN DAN DAMPAK KAMPANYE TERPADU - Trisyeling, Tansia (Universitas 17 Agustus 1945 Surabaya, 2025)
An integrated campaign, as part of Integrated Marketing Communication (IMC), plays a crucial role in delivering cohesive and impactful messages, as illustrated by the #PerempuanBermakna campaign by Asuransi Astra. This campaign aligns with strategic efforts to enhance gender equality and financial literacy, reflecting both societal and corporate priorities. By leveraging IMC, the campaign integrates digital and traditional media to connect with a broader audience, emphasizing the importance of coordinated messaging. This study aims to analyze the effectiveness of coordinated communication in influencing audience cognition, attitudes, and behaviors, as well as its long-term impacts. It is intended to serve as a reference for Asuransi Astra or other companies in designing future integrated campaigns. Using a literature review and document analysis, the study examines prior research and campaign data to evaluate message integration and audience responses. The #PerempuanBermakna campaign successfully raised awareness about women's roles in financial and health management, as evidenced by high engagement on social media and community participation in various events. Activities included seminars, social media challenges, and collaborations addressing breast cancer detection and financial education for female entrepreneurs. Employing the AMEC Framework, the campaign achieved clear objectives, significant audience reach, and measurable outcomes such as improved brand loyalty and enhanced financial literacy. The findings highlight that integrating social and financial themes increases the campaign’s relevance, while active community involvement amplifies its positive impact. However, the long-term effectiveness depends on the consistency between the campaign's messages and customer experiences with the services. This study underscores the importance of comprehensive message coordination in fostering meaningful engagement and achieving organizational objectives. Further analysis is necessary to explore the campaign's impact on decision-making habits and the sustainability of its outcomes. Keywords: Integrated campaign, Communication, Integrated marketing, Insurance